The Impact of Adult ADHD in the Quality of Life Profile. Issue 9 (July 2019) - Quintero, Javier; Morales, Isabel; Vera, Rosa; Zuluaga, Pilar; Fernández, Alberto
Objective: In this multicenter, cross-sectional study, we aimed to investigate the quality of life (QoL) and the neuropsychological and clinical characteristics of adults with ADHD with different developmental pathways.Method: Our study sample included 25 control (healthy) participants, 31 patients with newly diagnosed ADHD without comorbidities (ADHD-C-D), 31 with newly diagnosed ADHD with comorbidities (ADHD+C-D), and 29 with previously diagnosed ADHD with comorbidities (ADHD+C+D).Results: Compared with controls, ADHDs had little differences in the attentional performance but showed higher impulsivity, more severe symptoms of depression and anxiety, and lower QoL. The ADHD+C-D group showed more severe symptoms of depression and anxiety than the ADHD+C+D group ( p = .037 and p = .008, respectively), and poorer QoL in the psychological health sphere ( p = .003).Conclusion: Differences between ADHD and control subjects were particularly remarkable in mood symptoms and QoL. Previous diagnosis might have a positive impact on mood symptoms and QoL in ADHD adults.